Building to vehicle to building concept toward a novel zero energy paradigm: Modelling and case studies. (March 2019) - Barone, G.; Buonomano, A.; Calise, F.; Forzano, C.; Palombo, A.
Abstract: This paper proposes and analyses a novel energy management system for buildings connected in a micro-grid, by considering electric vehicles as active components of such energy scheme. Renewable energy sources, PV, energy storage systems and bidirectional electricity exchange with the buildings and the grid are taken into account. The considered energy scheme, Building to Vehicle to Building, is analysed by including both buildings and mobility consumptions in the energy balance. Three different management system scenarios, designed to analyse the role of electric vehicles as electricity vector among buildings integrating PV panels and electrical storages, are analysed through a case study analysis. To this aim, a dynamic simulation model, implemented in MatLab, is suitably developed for the assessment of the energy demands and loads of the building, as a function of the considered electric vehicles energy use patterns. Simulation results show that the proposed energy management systems improves the building grid reliance and the grid electricity consumption is remarkably reduced up to 45% and 77% depending on the proposed scenarios. Their energy exchange options also enhanced the energy-matching indexes. The economic analysis highlights the economic viability of the system, as well as the need of suitable funding policies to support the development of such micro-grid systems. Highlights: Modelling the impact of EVs toward the NZEB goal at micro-grid level. Investigating the electricity transfer among multiple buildings by the EV battery. Development of a dynamic simulation model of the proposed novel V2B energy scheme. Development of a case study analysis based on 3 generation and storage scenarios. Encouraging energy and economic performance of the proposed scheme are obtained.